2004
DOI: 10.1023/b:joec.0000017980.66124.d1
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Lemon Peel Constituents on Ceratitis capitata

Abstract: A series of experiments were conducted to evaluate the toxicity of lemon peel extracts incorporated into mediterranean fruit fly Ceratitis capitata diet. Extracts were obtained with different solvents: diethyl ether, ethyl acetate, and methanol. All three extracts were toxic to some extent; the diethyl ether extract was selected for further studies. Ether extracts of lemon peel were prepared weekly over a 2-month period, from fruits collected on the 1st d of the bioassay. Weekly GC-MS and UV analyses of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 2 publications
3
58
1
3
Order By: Relevance
“…The flavedo constitution is cited by several authors as the most critical resistance mechanism to fruit flies infestation in citrus (Back and Pemberton, 1915;Greany et al, 1983;Salvatore et al, 2004;Ioannou et al, 2012). Possibly, when oil glands in the flavedo are broken, they release toxic compounds that, in contact with eggs and first instar larvae, can cause death before the larvae reach the albedo region (non-oily region of the peel) (Greany, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The flavedo constitution is cited by several authors as the most critical resistance mechanism to fruit flies infestation in citrus (Back and Pemberton, 1915;Greany et al, 1983;Salvatore et al, 2004;Ioannou et al, 2012). Possibly, when oil glands in the flavedo are broken, they release toxic compounds that, in contact with eggs and first instar larvae, can cause death before the larvae reach the albedo region (non-oily region of the peel) (Greany, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Oil toxicity in the flavedo region for eggs and larvae of C. capitata can be attributed to the higher content of limonene in oranges . Salvatore et al (2004) evaluated egg viability of C. capitata laid in epicarp of four orange cultivars and found values between 19 and 49% of viability. The same authors found that citral compounds, coumarin and linalool, extracted from lime 'Sicilian' caused mortality of larvae of C. capitata of up to 98%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both natural as well as synthetic coumarins are in clinical trials for the treatment of various types of cancers because of their tendency to induce carcinoma cell apoptosis [14]. 5,7-Dimethoxycoumarin (Figure 1), a derivative of coumarin present in vegetables has shown potent anti-cancer activity through induction of DNA damage and inhibition of carcinoma cell proliferation [15,16]. The chemical structure of 5,7-dimethoxycoumarinindicates that it has potential to act as anti-oxidant agent.…”
Section: Introductionmentioning
confidence: 99%
“…Coumarins and their synthetic derivative compounds have been used in clinical trials, alone or in combination with traditional drugs such as etoposide, for the treatment of various malignant tumors, including renal, lung and kidney carcinoma as well malignant melanoma (6). A coumarin derivative, the 5,7-dimethoxycoumarin, has been identified in a small group of vegetable species, among which Citrus limon L. (7) and Carica papaya L. (8). This molecule showed both a differentiating effect on HL-60 cell line (9) and an inhibition activity in DNA adduct formation, induced by carcinogens, in mouse mammary gland (10).…”
Section: Introductionmentioning
confidence: 99%